Familial streptomycin ototoxicity in a South African family: a mitochondrial disorder. Issue 11 (November 1997) - Gardner, J C; Goliath, R; Viljoen, D; Sellars, S; Cortopassi, G; Hutchin, T; Greenberg, J; Beighton, P
Abstract : The vestibular and ototoxic effects of the aminoglycoside antibiotics (streptomycin, gentamycin, kanamycin, tobramycin, neomycin) are well known; streptomycin, in particular, has been found to cause irreversible, profound, high frequency sensorineural deafness in hypersensitive persons. Aminoglycoside ototoxicity occurs both sporadically and within families and has been associated with a mitochondrial DNA (mtDNA) 1555A to G point mutation in the 12S ribosomal RNA gene. We report on the molecular analysis of a South African family with streptomycin induced sensorineural deafness in which we have found transmission of this same predisposing mutation. It is now possible to identify people who are at risk of hearing loss if treated with aminoglycosides in the future and to counsel them accordingly. In view of the fact that aminoglycoside antibiotics remain in widespread use for the treatment of infections, in particular for tuberculosis, which is currently of epidemic proportions in South Africa, this finding has important implications for the family concerned. In addition, other South African families may potentially be at risk if they carry the same mutation.